Evaluación de la gestión técnica de los factores de riesgos físicos y su incidencia en la seguridad y salud ocupacional en los trabajadores de la Universidad Técnica de Cotopaxi del cantón Latacunga 2015. Manual de procedimientos de seguridad para riesgos físicos. - Carrión Eras, Jonathan Arturo (2016)
Technical University of Cotopaxi "UTC" education institution superior, concentrates students, servers, workers and teachers inside an infrastructure, where working risks are notorious and they can influence over coworkers. The used methodology on research study was exploratory investigation; the process was started since an investigated sample calculation producing as result 125 workers, after surveys were applied same which let to know generally physic risks those are presented on each working place, after measurements were made on high risk factors using calibrated measurement machines and results were tabulated and proved by actual working laws. Finally, is recommended a manual of procedures where working risks must be presented same which will help inside the university, creating a secure environment, the information that this thesis contains will be useful to get all placed objectives.